Implementasi Dashboard Penjadwalan Pengiriman Gas LPG Menggunakan Metode Distribution Requirement Planning untuk Meningkatkan Pemenuhan Pengiriman - Seto Sumargo; Prafajar Suksessanno Muttaqin; Yodi Nurdiansyah; Sherly Retyadi Desitasari; Anita Junianti; Alika Rahma Kadisha (Pusat Riset dan Inovasi Nasional, 2025)
Distribution is the process of moving, managing, and storing goods from suppliers to customers in the supply chain. This process includes not only the delivery of raw materials from suppliers to manufacturers, but also the distribution of finished products to the end consumer. Distribution plays an important role in a company's profitability because it affects operational costs, delivery efficiency, and perceived value by customers. Successful well-managed distribution will increase customer satisfaction and strengthen the company's competitiveness in the market. PT. XYZ is one of the LPG distributors that provides 3 kg cylinders. This company serves a variety of consumers, ranging from households, small businesses, to retailers, with a coverage of distribution areas in Serang City. The distribution process is carried out based on sales orders and needs in 14 bases, where each base has a different level of demand according to consumer needs. However, PT. XYZ faces obstacles in achieving the optimal level of service, where the average service level only reaches 97.40%. An imbalance between inventory and demand at the base often leads to an oversupply or understock, resulting in backorders on some demands. This condition has a negative impact on customer satisfaction and overall distribution effectiveness. To overcome this problem, PT. XYZ developed a distribution dashboard by applying the Distribution Requirements Planning (DRP) method. Through this approach, distribution planning becomes more systematic, base needs can be met appropriately, and stocks can be managed more effectively. This dashboard also supports delivery scheduling and more coordinated marketing activities. The results of the implementation of the DRP dashboard in 2023 show a significant increase with a service level that has successfully reached 99%, minimizing backorders, and increasing customer trust and satisfaction.